(untitled) (Fiep Bulletin - online, 2011)
Resistance exercises are presented as an effective stimulus for maintaining and increasing bone mineral density. The benefits of this type of training depend on the combination of the type of training, intensity, duration, type of exercise, weekly frequency, volume and order of exercises. However, there has been very clear what would be the best combination of these variables for a good bone response. Therefore, the aim of this study was to analyze the influence of the variables of resistance training on osteoporosis. The methodology used was to literature. The results showed that resistance training, when properly prescribed and directed, contributes to the prevention and treatment of osteoporosis. However, there are gaps to be investigated in relation to different combinations of resistance training on bone mineral density. Suggesting that more studies be conducted to compare experimentally the effects of variables of resistance training on osteoporosis.